"Playing by the Book": Determinants of Children's Preference for Replicating and Originating Play. (1st March 2019) - Van de Sompel, Dieneke; Vermeir, Iris
Abstract: Play is children's most important daily behavior and when children play, they do so in multiple ways. With two studies, this paper explores how children perceive a continuum of two play types, namely replicating play (in which models, guidelines, and examples are used to reach an intended result) and originating play (in which children create something from the mind, think freely about how they will play, are less restricted by given models, etc.). Study 1 ( N  = 56, M age  = 9) quantitatively shows that both play types occur and tests if children also describe the play types as we define them. Results show that children who play originating (vs. replicating) believe they follow less (vs. more) rules and do their own thing more (vs. less), which verifies the definitions of both types of play. Study 2 includes 16 in‐depth semi‐structured interviews ( M age  = 10) and shows which determinants children identify as triggers for engaging in play that has more replicating or more originating elements.